2014
DOI: 10.1088/0004-637x/785/1/19
|View full text |Cite
|
Sign up to set email alerts
|

NuSTARREVEALS AN INTRINSICALLY X-RAY WEAK BROAD ABSORPTION LINE QUASAR IN THE ULTRALUMINOUS INFRARED GALAXY MARKARIAN 231

Abstract: We present high-energy (3-30 keV) NuSTAR observations of the nearest quasar, the ultraluminous infrared galaxy (ULIRG) Markarian 231 (Mrk 231), supplemented with new and simultaneous low-energy (0.5-8 keV) data from Chandra. The source was detected, though at much fainter levels than previously reported, likely due to contamination in the large apertures of previous non-focusing hard X-ray telescopes. The full band (0.5-30 keV) X-ray spectrum suggests the active galactic nucleus (AGN) in Mrk 231 is absorbed by… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
106
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 92 publications
(116 citation statements)
references
References 98 publications
(194 reference statements)
10
106
0
Order By: Relevance
“…An alternative explanation for this discrepancy is that the AGN is intrinsically weak at X-ray wavelengths, as recently found by NuSTAR for the AGN in Mrk 231 (Teng et al 2014, see also Teng et al 2015).…”
Section: Agn Contribution To the Ir Luminositymentioning
confidence: 84%
“…An alternative explanation for this discrepancy is that the AGN is intrinsically weak at X-ray wavelengths, as recently found by NuSTAR for the AGN in Mrk 231 (Teng et al 2014, see also Teng et al 2015).…”
Section: Agn Contribution To the Ir Luminositymentioning
confidence: 84%
“…Di Pompeo et al (2013) found a statistical excess in mid-IR luminosities of radio-loud BAL QSOs. Moreover, studies based on NuSTAR observations showed that the hard X-ray emission (8-24 keV) of BALs tend to be intrinsically weaker than that of non-BALs (Luo et al 2014;Teng et al 2014), even though in a previous Chandra survey conducted by Gallagher et al (2006), it was inferred that that BALs and non-BALs have the same X-ray fluxes in the energy range of 0.8-8 keV once intrinsic absorption is taken into account. The same conclusion was reached by Weymann et al (1991) noticing the similarity of the optical emission lines of BALs and other QSOs.…”
Section: Discussionmentioning
confidence: 99%
“…BALQs do tend to show weaker X-ray emission (Brandt, Laor & Wills 2000), but generally by a factor of only 10-30. Recent high energy X-ray observations suggest the X-ray weakness is intrinsic and not due to absorption (Teng et al 2014). Furthermore, the recent study of Hamann et al (2013a) of mini-BALs with extreme velocity outflows, finds only weak X-ray absorption, which is not sufficient to prevent overionization.…”
Section: Introductionmentioning
confidence: 99%